2017
DOI: 10.1063/1.5001432
|View full text |Cite
|
Sign up to set email alerts
|

Performance and failure analysis of concentrator solar cells after intensive stressing with thermal, electrical, and combined load

Abstract: In this work, we investigated the impact of intensive heat loads on concentrator solar cells assemblies. As test samples, we employed lattice-matched and lattice-mismatched triple-junction solar cells made of GaInP/GaInAs/Ge. The thermal loads were induced by different manners. We used drying cabinets, external power supplies, and a combination of both to achieve maximum test temperatures of 180 °C. For the performance analysis, we utilized flash light solar simulators and an electroluminescence (EL) imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Whereas the effect of cell size on PMPP is not so clear than for PSSAT, microcells and larger cells have shown very good robustness under ASSAT. The difference between PSSAT and ASSAT can be explained by more aggressive stress conditions for thermal storage only, as previously reported by Eltermann et al, or by the thermal step at 230 °C required for cells mounting process used for ASSAT that may have slightly modified the cells [7].…”
Section: Electrical Performance Monitoringmentioning
confidence: 76%
See 3 more Smart Citations
“…Whereas the effect of cell size on PMPP is not so clear than for PSSAT, microcells and larger cells have shown very good robustness under ASSAT. The difference between PSSAT and ASSAT can be explained by more aggressive stress conditions for thermal storage only, as previously reported by Eltermann et al, or by the thermal step at 230 °C required for cells mounting process used for ASSAT that may have slightly modified the cells [7].…”
Section: Electrical Performance Monitoringmentioning
confidence: 76%
“…Whereas no catastrophic failure was observed, higher performance changes occurred in the PSSAT with a minimum PMMP/PMMP0 of 0.825 at the end of the test (up to 185 °C). Similarly, Eltermann et al have shown that thermal storage only, compared to thermal storage coupled with current injection and current injection only, led to the most severe degradation of the CPV cells [7]. However, using current injection in ageing tests is often considered as a correct stressing method by the CPV community to simulate photogeneration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiments at high humidity and temperature, oxidation of germanium and corrosion of the front side metallization occurred which is relevant for both structures. 210,211…”
Section: Designs For Low Module Height and Low Focal Distancementioning
confidence: 99%